(untitled) (International Journal of Physiotherapy, 2016)
Background: Energy cost of walking is two times higher in children with cerebral palsy when compared with normal children; this may be due to gait abnormalities.There is a negative influence on physical activity and early onsets of fatigue in activities of daily living are evident in cerebral palsy children and the reason for this is increase in energy cost of walking. Therefore, the treatment techniques which targets on correction of gait abnormalities and Energy conservation during walking are important to maintain orimprove independent functioning.The aim is to find out the effects of using Supra Malleolar Orthosis (SMO) along with co-activation exercise in the increase of gait endurance and also to encourage independent skills and abilities in cerebral palsy child. Methods: A 14 years child with spastic hemiplegic cerebral palsy was treated with custom made supra malleolar orthotic which was designed with an orthotic support followed with specific exercises, co-activating dorsiflexors and plantar flexors actively and with assistance. The subject was made to do the co-activation exercises 3 days per week for 8 weeks. Step length, stride length, cadence, navicular drop test, medial arch height and calcaneal eversion were measured before starting the treatment and at the end of 8th week. Results: the results of treatment shows that there is an improvement in 2 minutes’ walk test from 7(pre-test) to 13, step length from 22 (pre-test) to 32,stride length from 36(pre-test) to 47,cadence from 39 (pretest) to 37 after the use of Supra Malleolar Orthosis (SMO) and a co-activation exercises intervention. There was a clear and significant improvement noted in navicular drop test, medial arch height and calcaneal eversion after a period of 8 weeks use of orthosis and exercise intervention when compared with pre-test value. Conclusion: Orthotic subtalar alignment with co-acticvation exercises for alteration in gait endurance in a child is showing significantly good results in this case study of a child with cerebral palsy. The Co-activation exercise with Supra Malleolar Orthotic support reduces the intensity of symptoms and improved gait parameters in cerebral palsy child.